KINETIKA DAN SELEKTIFITAS SISTIM TRANSPOR Cu(II) ANTAR FASA MELALUI TEKNIK MEMBRAN CAIR FASA RUAH DENGAN MENGGUNAKAN OKSIN SEBAGAI ZAT PEMBAWA - -, Refinel; -, Zaharasmi; Tetra, Olly Norita (Universitas Andalas, 2010)
ABSTRACTThe effect of addition oleat acid 1.575 × 10-4M into membrane phase had been employed at the optimum condition of Cu(II) transport by the composition Cu(II) 3.15 × 10-4M as source phase with pH 3, oxine 17.5 × 10-4M dissolved into chloroform as membrane phase, H2SO4 0.15 M as receiving phase, stirring rate was 340 rpm. The result of the research showed increase in effectivity of transport Cu(II) interphase from 6 hours to 3 hours with the rate constants into membrane phase extraction (k1) 0.0454 minute-1, the stripping (k2) 0.0364 minute-1 at the temperature of 301°K and activation energy (Ea) 51.147 Kj/mol. The reaction was identified by means of kinetic model involving two consecutive irreversible first order. The selectivity of Cu(II) transport system analyzed to mixed Cu(II) ion with Cd(II), Co(II), Ni(II), Mg(II), Ca(II) and Sr(II) ions in pairing system or totaly system in 1 : 1 comparison. The measurement was performed to each ions that was transported receiving phase and the remains in resource phase by using SSA model Alfa-4. The result of research showed that Cu(II) was selective enough transported. Keywords: Kinetic transportation, Cu(II) ions, oxine, oleat acid, selectivity